THE APPLICATION OF COOPERATIVE LEARNING STRATEGY PEER TEACHING MODEL ON BIOLOGY LEARNING RESULT - INDAYANA FEBRIANI TANJUNG (VISION, 2017)
This study aims to determine the learning outcomes of biology learners on the material digestive system by using learning Cooperative Learning peer peerteaching model. The study was conducted at the State Islamic University of North Sumatra in mahapeserta biology semester 2 academic year 2016/2017. Data obtained from the ability mahapeserta educate do the pretest and postest questions. The learning process is done in accordance with peer peerteaching learning syntax. The results showed an increase in learning outcomes from pretest and posttest values.